2006
DOI: 10.1038/sj.ejcn.1602560
|View full text |Cite
|
Sign up to set email alerts
|

Muscularity and adiposity in addition to net acid excretion as predictors of 24-h urinary pH in young adults and elderly

Abstract: Objective: In patients with nephrolithiasis, an inverse relationship between 24-h urinary pH (24h-UpH) and body weight has been reported. Whether body composition indices and 24h-UpH are similarly associated in healthy subjects needs investigation. Design: Cross-sectional, retrospective analysis. Setting: Dortmund, Germany and Gothenburg, Sweden. Subjects: Healthy young adults (18-23 years; n ¼ 117) and elderly (55-75years; n ¼ 85) having a mean body mass index (BMI) of 22.8073.4 and 25.373.9 kg/m 2 , respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 31 publications
1
15
0
1
Order By: Relevance
“…On the other hand, if we consider urinary factors of lithogenic risk, an inverse correlation between pH and BMI and between pH and fat mass has been reported [7]. Moreover, the excretion of oxalate has been linked to body weight, body surface area and to lean mass [8].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, if we consider urinary factors of lithogenic risk, an inverse correlation between pH and BMI and between pH and fat mass has been reported [7]. Moreover, the excretion of oxalate has been linked to body weight, body surface area and to lean mass [8].…”
Section: Introductionmentioning
confidence: 99%
“…In recent papers, we studied total OA excretion rates in children and adolescents [3] as well as associations between anthropometry and acid-base parameters in young adults and elderly [18]. Based on the available OA measurements in adolescents [3] and complementary OA analyses in a group of elderly [18], we additionally examined whether higher protein intakes may have significant associations with urinary total OA excretion rates.…”
Section: Protein Intake and Oa Excretion -Find-ings In Adolescents Anmentioning
confidence: 99%
“…Based on the available OA measurements in adolescents [3] and complementary OA analyses in a group of elderly [18], we additionally examined whether higher protein intakes may have significant associations with urinary total OA excretion rates. In all subjects, protein intake was estimated from urinary total nitrogen excretion after allowing for potential correlated measurement errors as described elsewhere [19].…”
Section: Protein Intake and Oa Excretion -Find-ings In Adolescents Anmentioning
confidence: 99%
“…Notwithstanding the pseudoscientific extrapolation of the low-grade acidosis proposal into so-called alkaline diets by lay writers, intriguing prospective research has shown that dietary acid load increases subsequent risk of type 2 diabetes [244]. Acid load has also been linked to cardiovascular health [245], elevated body weight, increased waist circumference and a lower percentage of lean body mass [246-248]. …”
Section: Introductionmentioning
confidence: 99%